THE EFFECT OF NET INCOME AND OPERATING CASH FLOW ON TRADING VOLUME: A STUDY IN THE INDONESIAN STOCK EXCHANGE - ONG CHUN WIE, NIM.: 041113073 (2016)
The purpose of this research is to examine the effect of Net Income and Operating Cash Flow figures disclosed in the company’s annual reports to the demand of stock as represented by the Trading Volume records. The hypothesis is there is a significant statistical relationship between the figures to the demand of stock, as they represent the fundamental value of the stock. The sample is 630 annual reports of 210 companies which were listed in the Indonesian Stock Exchange for period 2012-2014. The empirical result shows that the level of Net Income and Operating Cash Flow has a (partially) significant but negative effect to Trading Volume. Therefore, it indicates that the investor consider financial information disclosed by the companies in annual reports as their base to make investment decision